Computer Aided Verification 35th International Conference, CAV 2023, Paris, France, July 17-22, 2023, Proceedings, Part III - Enea, Constantin; Lal, Akash (Lecture Notes in Computer Science, 2023)
The open access proceedings set LNCS 13964, 13965, 13966 constitutes the refereed proceedings of the 35th International Conference on Computer Aided Verification, CAV 2023, which was held in Paris, France, in July 2023. The 67 full papers presented in these proceedings were carefully reviewed and selected from 261 submissions. The have been organized in topical sections as follows: Part I: Automata and logic; concurrency; cyber-physical and hybrid systems; synthesis; Part II: Decision procedures; model checking; neural networks and machine learning; Part II: Probabilistic systems; security and quantum systems; software verification.